No more peaceful spring: An ecocritical reading of D. H. Lawrence Craving for Spring - Satria, Ridho Pratama; Septiani, Resty Maudina (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This research examines the representation of spring in D. H. Lawrence's poetry entitled “Craving for Spring”. This representation of spring is examined through the lens of ecocriticism theory and the theory of ecological consciousness found by Bannan-Watts. This research is evaluated by applying qualitative method to examine the data. The main data of the research are in the form of sentences related to ecological consciousness portrayed in the poem. This research found there are three kinds of ecological consciousness in the poem: (1) Comprehending the fundamental nature of the environment, (2) Recognizing the interconnectedness of human and nature. (3) Concerning about the condition of the nature. The result of this research indicates a shift in the meaning of spring. In the past, spring was depicted as natural harmony due to the rebirth of new plants after winter. Today, the meaning of spring has shifted. Spring does not represent the natural beauty. Spring becomes a season that brings fear to the people due to the natural disasters that emerge during spring.